AN ANALYSIS OF STUDENTS’ PHONOLOGICAL ERRORS IN PRONOUNCING VOWEL DIPHTHONGS - Rizky Mega Pertiwi; Dita Rizki Anggraini; Dio Resta Permana (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2026)
Abstract: Phonological errors remain a challenge for EFL learners, particularly in pronouncing English vowel diphthongs that differ from their first language. This study analyzes the types of phonological errors made by sixth-semester students at Universitas Indo Global Mandiri, identifies the most frequently mispronounced diphthongs, and examines the association between their understanding and pronunciation accuracy. A descriptive qualitative approach was employed with 26 participants. Data were collected through a pronunciation test and a questionnaire, then analyzed using phonetic transcription, descriptive statistics, and a Chi-Square test. Data trustworthiness was ensured through methodological triangulation involving pronunciation tests, questionnaires, and validation by an rater. The findings revealed 216 errors out of 936 attempts (23.1%), with misformation as the most frequent error (56.9%), followed by omission (40.7%), addition (2.3%), and no misordering. The diphthongs /əʊ/, /eɪ/, and /ɪə/ were the most problematic, largely due to articulatory complexity and the absence of equivalents in Bahasa Indonesia, while /ɔɪ/ showed the fewest errors. Statistical analysis confirmed no significant association between students’ theoretical understanding and pronunciation accuracy, indicating that knowledge alone does not guarantee accurate production. These findings highlight the need for pronunciation instruction to emphasize articulation training, auditory exposure, and repeated practice. Such approaches may help learners reduce persistent errors and enhance intelligibility in English communication, particularly within educational contexts.Keywords: phonological errors, pronunciation accuracy, surface strategy taxonomy, vowel diphthongs.